2019
DOI: 10.1111/jfpp.13947
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of spray drying conditions on the microencapsulation efficiency of pumpkin seed oil

Abstract: The aim of this study was investigating the effects of inlet drying air temperature, aspirator rate, and feed pump rate on microencapsulation of pumpkin seed oil (PSO). The laboratory spray dryer was used for microencapsulation of PSO. Gum Arabic, maltodextrin DE‐6, and whey protein concentrate were used as wall composition of the microcapsules. The dependent variables were moisture content (%W.b.), average particle size (µm), bulk density (kg/m3), microencapsulation efficiency (%), and peroxide value (meq/Kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 36 publications
0
9
0
5
Order By: Relevance
“…(2017) on microencapsulation of FO used the response surface method to optimize the operating conditions and documented the value of EE between 69.55% and 81.75%. The earlier studies have concluded that the predicted values of spray‐dried oil samples did not significantly differ from their actual values (Geranpour et al., 2019).…”
Section: Resultsmentioning
confidence: 93%
“…(2017) on microencapsulation of FO used the response surface method to optimize the operating conditions and documented the value of EE between 69.55% and 81.75%. The earlier studies have concluded that the predicted values of spray‐dried oil samples did not significantly differ from their actual values (Geranpour et al., 2019).…”
Section: Resultsmentioning
confidence: 93%
“…Se han reportado trabajos de secado por aspersión de aceites vegetales con contenidos de sólidos del 30 % para el café 29 , semilla de lino 30,31 , semilla de chía 14 , semilla de higo 32 , semilla de uva 33 , semilla de calabaza 34,35 , semilla de calabaza moscada 36 y semillas de colza-lino-cártamo 37 .…”
Section: Contenido De Sólidos Y Viscosidad De La Emulsión a Secarunclassified
“…A altas velocidades del flujo de gas, aumenta la EE. Esto pudo deberse a la rápida formación de una capa alrededor de las gotas como resultado de la cantidad de energía en la cámara de secado 35 .…”
Section: Velocidad Del Flujo De Gasunclassified
“…Many researches are being developed using the microencapsulation method. Thus, to protect oils from lipid oxidation [34][35][36], incorporating functional ingredients such as vitamins [37,38], additives and their storage protection [38], antioxidant protection [39].…”
Section: Instantizationmentioning
confidence: 99%